The Olival do Senhor dos Mártires necropolis (Alcácer do Sal, Portugal) in the context of the Iron Age funerary practices of the southwestern Iberian Peninsula. - Gomes, Francisco B. (2018)
The Olival do Senhor dos Mártires necropolis (Alcácer do Sal, Portugal) is one of the most relevant sites for the discussion of the Iron Age of Southern Portugal and, more specifically, of the funerary practices of that period in this territory. Unfortunately, and due to several circumstances, the available data is very incomplete and riddled with uncertainties. As an attempt to minimize these limitations, an integral study of the material from the necropolis is now underway; we present it here briefly, preceded by a global exposition of the research history and a cursory discussion of the available data.